Pain-Causing Venom Peptides: Insights into Sensory Neuron Pharmacology - Sina Jami; Andelain Erickson; Stuart M. Brierley; Irina Vetter (Toxins, 2017)
Venoms are produced by a wide variety of species including spiders, scorpions, reptiles, cnidarians, and fish for the purpose of harming or incapacitating predators or prey. While some venoms are of relatively simple composition, many contain hundreds to thousands of individual components with distinct pharmacological activity. Pain-inducing or “algesic” venom compounds have proven invaluable to our understanding of how physiological nociceptive neural networks operate. In this review, we present an overview of some of the diverse nociceptive pathways that can be modulated by specific venom components to evoke pain.